Chronic Traumatic Glass Foreign Body Removal from the Lung through a Direct Parenchymal Incision - Su Young Yoon; Si Wook Kim; Jin Suk Lee; Jin Young Lee; Jin Bong Ye; Se Heon Kim; Young Hoon Sul (Journal of Trauma and Injury)
Traumatic intrapulmonary glass foreign bodies that are missed on an initial examination can migrate and lead to severe complications. Here, we present a rare case of a traumatic intrapulmonary glass foreign body surgically removed by a direct pulmonary incision, which preserved the pulmonary parenchyma and avoided severe complications caused by migration.